Investigation on the formation of nitrogen, sulfur and chlorine species in air and oxy-fuel combustion of biomass in a semi-industrial combustion chamber - D. König; J. Ströhle; B. Epple (Fuel Processing Technology)
In this paper, the influence of oxy-fuel operation with flue gas recirculation on the occurrence of minority species in a semi-industrial combustion chamber is analyzed. The change of classical air combustion to an oxidizer mixture of O2 and flue gas in oxy-fuel combustion shows different changes in the formation of minority species like and SO2. This is due to the present of high levels of CO2 and a back feeding of this gaseous pollutant components into the combustion chamber through flue gas recirculation. In total, the changing formation mechanisms due to the presence of higher CO2 concentrations in the combustion chamber, leading to increased amounts of nitrogen, sulfur and chlorine based species. During oxy-fuel combustion, the formation of CS2 in the center of the flame is significantly higher, due to the availability of CO2. When comparing different oxygen concentrations in oxy-fuel flames, it is evident that the lowest oxygen concentration most closely resembles the air combustion case. This suggests that the overall formation of nitrogen, sulfur, and chlorine species and the burnout of those in the flame is highly dependent on the flame temperature. Therefore, a reduction in flame temperature leads to a corresponding decrease in the formation of these species in both air and oxy-fuel combustion scenarios.